Penguatan Branding Visual Dan Desain Kemasan Untuk Meningkatkan Daya Saing Produk UMKM - Agustriani, Fitri; Fauziyah, Fauziyah; Ningsih, Ellis Nurjuliasti; Febrianti, Amanda Astri Paratiwi (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service activity aims to provide training and mentoring through Strengthening Visual Branding and Packaging Design to increase the competitiveness of MSME products in Sungsang Village. The method used is training and mentoring for MSMEs processing fishery products, focusing on crackers, pempek, and shrimp otak-otak. The activity stages include product identification, packaging technology training (education on the role of packaging on quality and branding, as well as training on the use of heat sealers, vacuum sealers, and label design), direct application, and monitoring of production results. The results showed that the training on visual branding and packaging design, as well as the introduction of vacuum sealer technology and label design, successfully added value to the product. Participants stated that products with new designs have more appeal and increased self-confidence for marketing through online media (Instagram, TikTok, WhatsApp). This activity emphasized the importance of Brand Identity which can increase sales value and expand the marketing of MSME products.Abstrak: Kegiatan pengabdian ini bertujuan memberikan pelatihan dan pendampingan melalui Penguatan Branding Visual dan Desain Kemasan untuk meningkatkan daya saing produk UMKM di Desa Sungsang. Metode yang digunakan adalah pelatihan dan pendampingan kepada UMKM pengolah hasil perikanan, berfokus pada kerupuk, pempek, dan otak-otak udang. Tahapan kegiatan mencakup identifikasi produk, pelatihan teknologi kemasan (edukasi tentang peran kemasan terhadap kualitas dan branding, serta pelatihan penggunaan heat sealer, vacuum sealer, dan desain label), penerapan langsung, dan monitoring hasil produksi. Hasilnya menunjukkan bahwa pelatihan branding visual dan desain kemasan, serta pengenalan teknologi vacuum sealer dan desain label, berhasil memberikan value added pada produk. Peserta menyatakan produk dengan desain baru memiliki daya tarik lebih dan meningkatkan kepercayaan diri untuk pemasaran melalui media online (Instagram, TikTok, WhatsApp). Kegiatan ini menekankan pentingnya Brand Identity yang dapat meningkatkan nilai jual dan memperluas pemasaran produk UMKM.